Analisis Dampak Penerapan E-Procurement Pada Pemerintah Provinsi Banten - Kusnadi, Endang; Haerofiatna, Haerofiatna; Syaechurodji, Syaechurodji; Setiani, Henny (Jurnal Ilmiah Sains dan Teknologi, 2023)
Presidential Regulation no. 54 of 2010 concerning government procurement of goods/services,namely to increase transparency and accountability, increase market access and healthy businesscompetition, improve the level of efficiency of the procurement process, support the monitoringand audit process, and meet the need for real-time access to information. This is the main goal ofthe government, especially Banten Province, in implementing e-procurement in the process ofprocuring goods and services. However, it is not yet known which impact of this achievement hasthe highest weight of success in increasing the transparency and performance of the BantenProvincial Government, making it easier for leaders to carry out evaluations. This is the mainfactor in researching the impact of e-procurement using the Analytical Hierarchy Process (AHP)method so that we can find out the level of success of e-procurement that is most dominantly feltby the Banten Provincial Government by the presidential decree.